2021
DOI: 10.1111/obr.13218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different training modalities on anthropometric outcomes in patients with obesity: A systematic review and network meta‐analysis

Abstract: Summary Obesity management guidelines consistently advise aerobic training for weight loss, whereas recommendations for other training modalities are sparse. This systematic review and network meta‐analysis (NMA) aimed to compare the long‐term effects of different training modalities on anthropometric outcomes in patients with obesity. MEDLINE, Cochrane CENTRAL, and Web of Science were searched to identify the following: (1) randomized controlled trials (RCTs); (2) conducted in adults with a mean body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 81 publications
6
28
0
2
Order By: Relevance
“…Our findings that resistance training alone and combined resistance and aerobic exercise can significantly reduce fat mass were in agreement with previous systematic reviews and meta‐analyses 5,7,140 . However, among the interventions investigated in this study, resistance‐based exercise programs combined with caloric restriction were the most effective for reducing body fat percentage and whole‐body fat mass in participants who are overweight or obese.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings that resistance training alone and combined resistance and aerobic exercise can significantly reduce fat mass were in agreement with previous systematic reviews and meta‐analyses 5,7,140 . However, among the interventions investigated in this study, resistance‐based exercise programs combined with caloric restriction were the most effective for reducing body fat percentage and whole‐body fat mass in participants who are overweight or obese.…”
Section: Discussionsupporting
confidence: 93%
“…Although greater effects were observed when undertaking resistance training or combined resistance and aerobic exercise, as previously reported, 5,7 the result that resistance training can at least help preserve lean mass while undergoing caloric restriction is meaningful for this population. In the systematic review of Weinheimer et al, 149 the authors reported that ~70% of studies only undertaking caloric restriction present reductions ≥1.5 kg of lean mass in middle‐aged and older adults.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our findings also indicate that muscle mass can be effectively maintained or muscle mass loss can be prevented by the adjunct therapy of RET in individuals with obesity and OA who are undergoing a dietary weight loss intervention. Finally, a previous NMA indicated that RET and MET are equally ranked as optimal exercise therapies for muscle mass gain in adults with obesity [101], which supports the present study finding that RET and MET combined with diet therapy were ranked as the first two optimal treatments for individuals with obesity and knee or hip OA. We further identified that PMMR plus RET had the highest efficacy for muscle mass gain over a short-term follow-up, and PMMR-DIA plus MET had the strongest long-term effect on muscle mass and walking speed outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings indicate that the efficacy of diet therapy for muscle mass can be objectively estimated using percentage LBM or FFM rather than absolute values. Second, previous systemic review studies have indicated that muscle strength training, especially RET, augments muscle mass gain in older people with sarcopenia [99,100], individuals with obesity and OA [101], and older adults with OA [24]. The muscle mass gain caused by exercise may be beneficial for older adults with obesity who are undergoing weight management [31,102].…”
Section: Discussionmentioning
confidence: 99%